Gross movement patterns in elite female volleyball - Perez-Turpin, J.; Cortell-Tormo, J.; Suarez-llorca, C.; Chincilla-Mira, J.; Cejuela-Anta, R. (Kinesiology, 2009)
Recent research has shown the developments made in the analysis of gross movement patterns in tennis, but such research has yet to be extended to the field of beach volleyball. This study was designed to develop a method for analysing gross movement patterns so as to quantify movement types and their relationship to real competition and performed during the European Beach Volleyball Championships held in Valencia (Spain) in 2006, using the SportsCode analysis software. The aim of the study was to compare gross movement types and patterns in female professional beach volleyball. A quantitative analysis of beach volleyball play was carried out on 10 players taking part in the aforementioned volleyball championship, using video recordings of the 1,646 movements that were registered in four matches played. The recordings were analysed using SPSS ver. 13.0. Chi-square tests showed significant differences between the types of gross moves. The first result of the analysis showed that female players used the offensive movement patterns (OMPs) 59% of the time (p?.001), and the defensive movement patterns (DMPs) 41% of the time. The second result showed that 24% of the DMPs were receptions, 29% (p?.05) were blocks, and 47% (p?.001) were defence moves. The final analysis showed that 34% (p?.001) of the OMPs were placements, 50% (p?.001) were attacking moves, and 16% were attack preparation moves. Identifying and understanding DMPs and OMPs in female toplevel players is vital for defining specific and effective beach volleyball training strategies.